The Influence Of Brand Image, Packaging, And Promotion On Purchasing Decisions For Mineral Water King Oseng At CV. Maju Terus Bahagia Sejahtera Sentosa Banyuwangi - Indah May Sary; Agus Riyanto; Moh. Fahrurrozi (International Publisher (YAPENBI), 2024)
This study aims to analyze the effect of brand image, packaging and promotion on purchasing decisions for King Oseng Mineral Water products at CV. Maju Terus Bahagia Sejahtera Sentosa Banyuwangi, both simultaneously and partially. The population in this study were customers of King Oseng Mineral Water products at CV. Maju Terus Bahagia Sejahtera Sentosa Banyuwangi. The sampling method used is nonprobability sampling, data collection using purposive sampling. The data was collected using a questionnaire in which the sampling was 40 respondents. This type of descriptive quantitative research uses instrument tests, classical assumption tests, multiple linear regression analysis, hypothesis testing (T & F tests), and the coefficient of determination. The results in this study show that the brand image (X1), packaging (X2) and promotion variables (X3) simultaneously (F test) have a positive and significant influence on purchasing decisions. While the results partially (T test) that the brand image variable has no effect and is insignificant to purchasing decisions, the packaging variable has no effect and is insignificant to purchasing decisions, and the promotion variable has a positive and significant effect on purchasing decisions. With the coefficient of determination (Adjust R Square) obtained of 0.474 or 47.4%. This means that 47.4% of purchasing decisions can be explained by independent variables, while the remaining 52.3% is likely to be explained by other independents that are not included in this study.